2011
DOI: 10.1144/0016-76492010-123
|View full text |Cite
|
Sign up to set email alerts
|

The emplacement of the Palaeogene Mourne Granite Centres, Northern Ireland: new results from the Western Mourne Centre

Abstract: There is a basic assumption that the upper crustal point of magma emplacement overlies the point where magma was generated. This contribution discusses the concept of lateral magma movement in the upper crust based on the Mourne Granite Centres, Northern Ireland. We report anisotropy of magnetic susceptibility fabric data from the Western Mourne Centre that indicate SSW to NNE inflow in this centre, parallel to the Eastern Centre. This suggests that these two centres share a common feeder zone outside the Mour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Permian, Triassic, Jurassic and Cretaceous sequences are found in north-east Ireland's Rathlin Trough and Lough Neagh-Larne Basin (McCann, 1988(McCann, , 1990Naylor, 1992) Naylor, 1992). Tertiary igneous complexes relating to the rifting of North America and Eurasia and the opening of the Atlantic Ocean are present in north-east Ireland (Jolley and Bell, 2002;Stevenson and Bennett, 2011). The vast basaltic lavas of Co. Antrim date to this period (Lyle, 1980;Lyle and Preston, 1993), whilst the Mourne granites of Co. Down were also emplaced at this time (McCormick et al, 1993;Stevenson and Bennett, 2011).…”
Section: Post-variscanmentioning
confidence: 99%
“…Permian, Triassic, Jurassic and Cretaceous sequences are found in north-east Ireland's Rathlin Trough and Lough Neagh-Larne Basin (McCann, 1988(McCann, , 1990Naylor, 1992) Naylor, 1992). Tertiary igneous complexes relating to the rifting of North America and Eurasia and the opening of the Atlantic Ocean are present in north-east Ireland (Jolley and Bell, 2002;Stevenson and Bennett, 2011). The vast basaltic lavas of Co. Antrim date to this period (Lyle, 1980;Lyle and Preston, 1993), whilst the Mourne granites of Co. Down were also emplaced at this time (McCormick et al, 1993;Stevenson and Bennett, 2011).…”
Section: Post-variscanmentioning
confidence: 99%
“…For example, Stevenson et al . [] and Stevenson and Bennett [] used AMS fabrics to demonstrate that the Mourne Mountains (NE Ireland) granite intrusions were emplaced laterally, instead of forming through in situ cauldron subsidence related to caldera collapse. Regardless of source, studies of various intrusive elements of the BPIP have documented lateral movement of magma over many 10's of kilometers away from the magma ascent site.…”
Section: Discussionmentioning
confidence: 92%
“…The granite pluton has been treated as two separate magmatic centers, an eastern and western center ( Fig. 2A) (Emeleus, 1955;Hood, 1981;Gibson, 1984;Meighan et al, 1984;Cooper and Johnston, 2004;Stevenson et al, 2007;Stevenson and Bennett, 2011 mapping has shown that the granites form a connected pluton (Richey, 1927;Emeleus, 1955;Hood, 1981;Gibson, 1984). The oldest granites, G1 to G3, form the eastern part of the pluton, and the younger granites, G4 and G5, form the western part ( Fig.…”
Section: The Mourne Mountains Magmatic Centermentioning
confidence: 99%
“…Richey (1927) therefore interpreted the northeastern contact to the Eastern Mourne pluton to represent part of the feeding ring dike to the granite pluton. Stevenson et al (2007) and Stevenson and Bennett (2011) analyzed magnetic (AMS) fabrics in the Mourne Mountains granites. The magnetic fabric in the Mourne granite pluton is dominantly oblate to triaxial.…”
Section: The Mourne Mountains Magmatic Centermentioning
confidence: 99%